Síntese de triazolopirimidinas 7-triclorometil e triazolopirimidinonas substituídas a partir de reações entre 4-alcóxi-1,1,1-tricloro-3-alquen-2-onas e 3-amino-1H-1,2,4-triazóis - Souza, Laura de Andrade (2013)
A synthetic strategy was developed for obtaining a series of new 7- trichloromethyl-[1,2,4]-triazolo-[1,5-a]pyrimidines substituted from cyclocondensation reaction between 4-alkoxy-1,1,1-trichloro-3-alken-2-ones (enones 1) of the general formula: RO-C(R2)=C(R1)C(O)CCl3 (where R = Me, Et, R1 = H, Me, R-R1 = -(CH2)2, - (CH 2)3- and R2= H, Me, C6H5, 4-F-C6H4, 4-OMe-C6H4) and 3-amino-1H-[1,2,4]triazol- 5-substituted (H (2), CO2H (3), SMe (4)) via a single step reaction using a simple and efficient method. In a second step, in order to exploit the synthetic versatility of the trichloromethyl group, were performed cyclocondensation reactions in basic medium using the enones 1 and 3-amino-1H-[1,2,4]triazole (2-4) to obtain a series of 1,2,4- triazolo-[1,5-a]pyrimidinones. The 7-trichloromethyl-[1,2,4]triazolo-[1,5-a]pyrimidines and 1,2,4-triazolo-[1,5- a]pyrimidinones were obtained from 50% to 85 % yield, and purified by recrystallization from ethanol. The reaction of enones 1 with 3-amino-1H-[1,2,4]- triazole-5-carboxylic acid 4 led to the formation of the respective triazolopyrimidines, however, under all reaction conditions tested, decarboxylation of the triazole was observed. The most cyclocondensation reaction of enones 1 with 3-amino-1H-[1,2,4] triazole (2,3) led only to obtain the 2,7-isomer of the 1,2,4-triazolo-[1,5-a]pyrimidines. With some enones it was observed the formation of a small amount the 2,5 isomer. As for the triazole pyrimidinones were formed on both isomers depending enone used. The products obtained in this work were characterized by Nuclear Magnetic Resonance of Hydrogen and Carbon-13, Mass Spectrometry and its degree of purity proven via Elemental analysis was also possible to establish some structures by Xray diffraction.